A sensitive non-enzymatic immunosensor composed of silver nanoflowers for squamous cell carcinoma antigen. Issue 4 (12th January 2017) - Li, Yueyun; Zhang, Yihe; Han, Jian; Chu, Paul K.; Feng, Jinhui; Dong, Yunhui
Abstract : In this work, a sensitive sandwich-type non-enzymatic electrochemical immunosensor for quantitative detection of squamous cell carcinoma antigen (SCCA) is designed and fabricated. Abstract : In this work, a sensitive sandwich-type non-enzymatic electrochemical immunosensor for quantitative detection of squamous cell carcinoma antigen (SCCA) is designed and fabricated. Gold nanoparticles/graphene nanoribbons (Au NPs/NH2 –GNRs) are used as the platform of electrochemical immunosensor to accelerate electron transfer and increase the specific surface area. The Au NPs with good biocompatibility can increase the probability of capturing primary antibodies (Ab1 ) to further improve the sensitivity. The silver nanoflower–molybdenum disulfide/multiwalled carbon nanotubes (SNFs–NH2 –MoS2 /MWCNTs) were used as labels of secondary antibodies (Ab2 ) and exhibit remarkable multiple-signal amplification effects. The silver nanoflowers with many branches can provide abundant active sites for the electrochemical reaction to further improve the sensitivity. Under the optimal conditions, the immunosensor shows a wide linear range between 0.1 pg mL −1 and 20 ng mL −1 with a limit of detection 0.03 pg mL −1 . Furthermore, the novel immunosensor shows good performance for the detection of serum samples. The results indicate that the proposed immunosensor could be promising in the clinical application for quantitative detection of SCCA.